Assessing the Efficiency of intraosseous suturing in treating gingival smile patients caused by muscular hyperactivity (clinical study) - خطاب, احمد (Latakia University Journal -Medical Sciences Series, 2023)
Background and Objectives: Gingival smile is one of the most common deformities among patients with high aesthetic requirements especially for younger ages. being considered mainly challenging for surgeons for requiring several surgeries to achieve satisfactory results in their aesthetic aspect. Despite the numerous approaches for this, no one approach is right for all cases that outweigh others. The study aims to assess the efficiency of the intraosseous suturing technique in treating gingival smile cases, this procedure can be performed in one surgical step with little to no risk of relapse, and no extra measurements needed. Material & Methods: The sample consisted of 20 patients with a gingival smile. Undergone surgical correction using intraosseous suturing technique. The samples were documented with consecutive photographs spanning over six months and twelve months after the surgery. Photographs were also analyzed by anthropometry analysis to measure lip level in relation with central incisors and the protrusion of the upper lip during smiling. Paired Samples test was conducted and with P value <0.05 Results: Results showed an improvement in the variables during the follow-up period. The patients in the sample maintained a consistent improvement in the aesthetic aspect. Conclusion: Within the limits of this study, Intraosseous suturing technique in treating gingival smile patients has shown to be effective, showing consistent clinical results throughout the follow-up period in terms of Key Words: Gingival smile, Intraosseous suturing KeyWords: Gingival smile, Intraosseous suturing, muscular hyperactivity